35 - ATTENTIONAL TRAINING: EFFECTS ON SHORT-TERM MEMORY IN INDIVIDUALS WITHIN THE AGING PROCESS. (Fiep Bulletin - online, 2011)
Evidence indicates certain kinds of mental exercises and life style as lessening the memory retrogenic process. This perspective was adopted for a memory exercises training aimed at improving attentional processes, and consequently, short-term memory performance and mental processing for a group of 24 individuals, aged from 65 to 85 years. Post exercises improvement was examined by the Carvalho (2006) protocol and a test called SKT (ERZIGKEIT, 2001) was used in measuring the mental processing factor. The non-parametric statistics used for the scores analysis revealed to be significant with the signal tests index z = 3, 27 (0.05) > 1, 96, p 0.05).
Keywords: Attention; Short-term memory; Memory training